Battery Discharge Characteristics in a Modified Electric Bicycle: Karakteristik Pengosongan Baterai pada Sepeda Listrik yang Dimodifikasi - Arif Wisnu Isha Mahendra; A’rasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The increasing use of petroleum-fueled transportation has intensified concerns regarding air pollution and the need for alternative energy-based mobility systems. Specific Background: Electric bicycles represent a practical short-distance transportation option, and battery performance becomes a critical factor in determining their operational capability. Knowledge Gap: Although electric bicycles are increasingly discussed, limited experimental studies directly compare dry batteries and wet batteries under different load and travel-distance conditions in simple electric bicycle modifications. Aims: This study aims to evaluate the power consumption characteristics of a modified electric bicycle by varying load and travel distance using dry and wet batteries. Results: Experimental testing was conducted using 50 kg and 60 kg loads over distances of 200 m, 300 m, and 400 m. The findings show that greater load and longer travel distance increased battery power consumption. For the dry battery, the lowest power consumption was 0.24 V at 50 kg and 200 m, while the highest was 0.97 V at 60 kg and 400 m. For the wet battery, the lowest value was 0.37 V at 50 kg and 200 m, while the highest reached 1.12 V at 60 kg and 400 m. Novelty: The study provides direct comparative experimental evidence of discharge behavior between dry and wet batteries in a simple modified electric bicycle under controlled load-distance variations. Implications: These findings contribute useful engineering insight for selecting battery types and operating conditions in small-scale electric bicycle development. Keywords: Electric Bicycle, Battery Performance, Power Consumption, Load Variation, Travel Distance Key Findings Highlights Higher load consistently increased electrical energy usage during operation. Longer travel routes produced greater voltage reduction in both battery types. Wet-cell storage showed the largest discharge under the heaviest testing condition.